Developing Locally-Sourced Descriptive Reading Materials For The Senior High School Students In Maluku Barat Daya: A Pedagogical Approach - Anmama, Ronald Paiter; Maruanaya, Hendrik J.; Meyer, Fredi (Prodi Pendidikan Bahasa Inggris, Program Studi Diluar Kampus Utama (PSDKU) Unpatti-MBD, 2024)
Students need to gain familiarity with the content of learning materials is one of the various classroom problems that influence EFL students' learning activities. The purpose of this study was to develop local content-based descriptive reading materials for the tenth-grade students of SMA Negeri 13 MBD. The ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation, was used for the instructional development of the descriptive reading materials. Three units of locally relevant reading materials and activities were developed, and they underwent expert review, a pilot test with a small group for usability, and a field evaluation with 35 tenth-grade students of SMA Negeri 13 MBD. The data were collected using questionnaires, interviews, and tests. The implementation of the developed local content-based descriptive reading materials with the local tenth-grade EFL students resulted in a significant improvement in their reading skills and motivation.